1992
DOI: 10.1177/095632029200300308
|View full text |Cite
|
Sign up to set email alerts
|

Purine Arabinosides as Inhibitors of Human Haemopoietic Progenitor Cells

Abstract: SummaryFour purine arabinosides that inhibit varicella-zoster virus (VZV)replication in vitro were tested as inhibitors of colony formation by progenitor cells from normal human bone marrow. In general, erythroid burst forming cells (BFU-E) were more sensitive to inhibition by . these compounds than were either erythroid colony forming cells (CFU-E) or granulocyte/macrophage colony forming cells (CFU-GM). A 50% reduction in colony formation (IC so ) was observed for BFU-E in the presence of 8 fLM 6-methoxypuri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

1992
1992
1992
1992

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…In addition, enzyme studies have shown that ara-M is a substrate for ADA, yielding ara-H as its product (3). High levels of ADA in the intestines of rats, as well as other animals (14), would expose ara-M to this enzyme during absorption and, therefore, could explain the marked difference in the extent of ara-M metabolism after intravenous and oral dosing.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, enzyme studies have shown that ara-M is a substrate for ADA, yielding ara-H as its product (3). High levels of ADA in the intestines of rats, as well as other animals (14), would expose ara-M to this enzyme during absorption and, therefore, could explain the marked difference in the extent of ara-M metabolism after intravenous and oral dosing.…”
Section: Discussionmentioning
confidence: 99%
“…One group of orally dosed rats was treated with EHNA (50 mg/kg; intraperitoneally) at 1 h predose and at 3 and 6 h postdose, and the other group was not pretreated. Blood samples were obtained from each animal at 2, 5, 10, 20, 40, and 60 min and 1.5, 2.0, 2.5, 3.0, 4.0, 5.0, and 6.0 h postdose. Blood samples (0.4 to 0.5 ml) were withdrawn through the cannula into syringes containing EDTA.…”
mentioning
confidence: 99%
“…Enzyme and in vivo studies indicate that adenosine deaminase catabolizes 1 to hypoxanthine arabinoside, which is then excreted or further metabolized (Averett et al, 1991b;Burnette et et., 1991). A significant first-pass effect was indicated by the dramatic differences in urinary recovery of unchanged 1 following oral and intraperitoneal administration (Burnette et al, 1991).…”
Section: -Methoxypurine Arabinoside (9-[i3-d-arabinofuranosyl]mentioning
confidence: 99%
“…This arabinoside is metabolized by adenosine deaminase to hypoxanthine arabinoside (Averett et al, 1991b), which in turn, can undergo phosphorolysis to hypoxanthine and arabinose-1-phosphate by the action of purine nucleoside phosphorylase (Stoeckler et el., 1980). Both of these catabolic reactions are rather sluggish in vitro compared to the action of these enzymes on their natural nucleoside substrates.…”
mentioning
confidence: 99%